Gingival health and relapse tendency: a prospective study of two types of lower fixed retainers - Al-Nimri Kazem; Habashneh Rola Al; Obeidat Mohammed (Sciendo, 2023)
Different types and diameters of wire are used in bonded lingual retainers. Some clinicians bond a small diameter multistrand wire to each tooth, while other clinicians bond a large diameter wire to the lingual surfaces of the lower canines.